MAPPING OF POSYANDU SERVICES FOR YOUTH USING ArcGIS: SPATIAL ANALYSIS OF POSYANDU FOR YOUTH IN BATAM CITY - Amir, Eka Fitri; Marzuki, Asep; Panggabean, Septi Maisyaroh Ulina; Sianipar, Yola Abdila (Fakultas Kesehatan Universitas Muhammadiyah Sumatera Barat, 2025)
Background: Adolescents are a group that is vulnerable to health problems due to risky behavior. In fact, the presence of youth posyandu in the midst of society does not guarantee the achievement of national health targets, there are many obstacles in its implementation. The aim of this research is to provide data in the form of visualization maps using website-based ArcGIS so that website users can find out information on the location and programs of youth posyandu in Batam City, With information on youth Posyandu visualization, it is hoped that it will be able to increase youth participation and interest in youth Posyandu activities. The method used in this research is the development of a Geographic Information System (GIS) using ArcGIS, namely an application for mapping and visualization of location information, infrastructure and the effectiveness of the youth posyandu program in Batam City. Data was collected by conducting surveys and literature studies then identifying spatial patterns. Research results based on development and survey results show that the number of youth posyandu in Batam City is Youth Posyandu spread across 12 sub-districts and 21 Community Health Centers in Batam City which have been visualized in the form of location maps and there has been an increase in youth participation in posyandu activities. Conclusion: The youth posyandu data has been interpreted into ArcGIS and can be displayed using open stretch maps, Google Maps visualization options or satellite visualization of youth posyandu data in Batam City.